Bimbingan Teknis Pengolahan Telur Asin Rempah Panggang pada PKK Ruhuy Rahayu Desa Bentok Kampung Kecamatan Bati – Bati Kabupaten Tanah Laut Kalimantan Selatan: Roasted Salted Eggs with Spices Processing Technical Guidance at PKK Ruhuy Rahayu Bentok Kampung Village, Bati – Bati District, Tanah Laut Regency, South Borneo Province - Sugiarti Sugiarti; Fitriani Fitriani; Siti Dharmawati (Fakultas Peternakan Universitas Papua, 2021)
ABSTRACT Bentok Kampung Village is one of the villages in Bati–Bati District, Tanah Laut Regency, which possessed a considerabke amount of duck population. The villagers who are members of the Ruhuy Rahayu PKK do not know much about innovations in processing duck salted eggs. This activity aims to introduce innovation in preserving duck eggs with the addition of spices. This activity started with theoretical training with classroom methods and hands-on practice carried out by partners under the guidance of the activity promotor team. The enthusiasm of the participants is was quite good which was reflected in the high number of participants and their punctuality of attendance. The attendance level of participants in both the counseling and brainstorming activities reached 90–100% of all PKK members. The roasted salted duck eggs with spices produced have a distinctive taste compared to the ones which were just boiled. The roasted spiced salted roasted egg has a less wet texture and is preferred because it tastes more savory and can last longer because of the reduced water content. Conclusion: participants managed to understand well the entire series of activities and the participation rate of participants was very good with a nearly 100% attendance rate. Keywords: Processing, Roasted spiced salted eggs, Bentok Kampung Village ABSTRAK Desa Bentok Kampung merupakan salah satu desa yang ada di Kecamatan Bati–Bati Kabupaten Tanah Laut dengan populasi itik yang tinggi. Masyarakat Desa Bentok Kampung yang tergabung dalam PKK Ruhuy Rahayu belum banyak mengetahui inovasi dalam pengolahan telur asin itik. Kegiatan ini bertujuan untuk meperkenalkan inovasi pengawetan telur itik dengan penambahan bahan rempah. Kegiatan ini diawali pelatihan teoritis dengan metode kelas dan praktek langsung yang dilaksakanakan oleh mitra dengan bimbingan tim pengusul kegiatan. Antusisme peserta cukup baik yang tercermin dari jumlah dan ketepatan waktu kehadiran yang tinggi. Kehadiran peserta dalam kegiatan penyuluhan dan curah pendapat mencapai 90–100 % dari seluruh anggota PKK. Telur asin itik rempah panggang yang dihasilkan memiliki cita rasa yang khas dibandingkan dengan yang hanya direbus. Telur asin itik rempah panggang memiliki tekstur tidak terlalu basah dan lebih disukai karena rasanya yang lebih gurih dan bisa lebih tahan lama karena adanya pengurangan kadar airnya. Kesimpulan: peserta berhasil memahami dengan baik seluruh rangkaian kegiatan dan tingkat partisipasi peserta sangat baik dengan tingkat kehadiran berkisar 100%. Kata Kunci: Pengolahan, Telur asin rempah panggang, Desa Bentok Kampung